POLITIK HUKUM PRODUK MUSYARAKAH PADA BANK SYARIAH: STUDI KEBIJAKAN DALAM FIKIH DAN FATWA DSN - Rosida, Rosida (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
The increase of Islamic Bank in Indonesia is to fast, we can indentify that the industry is grow up di every sektor and teritory, every where. Inside ther Islamic Bank have a anykind of the product. Example we call mudharabah, bai-Salam dan musyarakah. In this paper we more analyst the musyarakah product with Politik Hukum perspektif. Politik Hukum is a science that learn what the considern abaout law produt like regulation, new or past regulation that we erased. This research using metodology kualitatif and analitical describtion. The source of data using three data there is primery data, secondary data and third data. Globaly this reseacrh was finding a deferrence of musyarakah at fikih and Fatwa DSN with any considern it self.